A study on dynamic capabilities view of doctoral students’ research productivity - Muneeb, D.; Tehseen, Shehnaz *; Saeed, K. (Emerald, 2019)
Purpose: The purpose of this study is to investigate the influence of dynamic capabilities (DC) along with operational capabilities such as network orientation, academics, social networking and perceived supervisory support (PSS), on the research productivity of doctoral students in Malaysia and the United Arab Emirates (UAE). Design/methodology/approach: Data were collected through an online quantitative survey from participants recruited via snowball and quota sampling. The conceptual model was developed and tested using partial least squares structural equation modelling. Findings: DC, network orientation and academic and social networking are shown to have a positive influence on the productivity levels of doctoral students in Malaysia and the UAE. However, the influence was found to be stronger in the Malaysian sample than in the UAE sample. The impact of PSS was not seen to be statistically significant in either sample. Practical implications: The findings suggest that attention needs to be paid to strengthening doctoral students’ DC in terms of research skills and competencies, as well as enhancing operational capabilities to improve students’ research capabilities. Originality/value: Drawing on strategic management approaches and socialisation theory, this study is assumed to be the first that considers doctoral students’ research productivity in the context of DC.